2020
DOI: 10.1186/s12985-020-01391-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of severe fever with thrombocytopenia syndrome viruses from tick and bitten patient in Southeast China

Abstract: Background: Severe fever and thrombocytopenia bunyavirus (SFTSV) infection causes severe fever and thrombocytopenia syndrome with high mortality. It is extremely rare that a transmitting tick can be directly captured in bite wounds, and that SFTSV can be isolated from both the captured tick and patient's serum to establish a solid pathogen diagnosis. Case presentation: We report a case infected with severe fever and thrombocytopenia bunyavirus. The 69year-old male patient presented with fever and tenderness on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The presented results strongly support the link between SFTSV-infected ticks and the patient with SFTS with a history of tick bites. Some studies have identified SFTS pathogens in engorged ticks from patients with SFTS in the ROK and China (Wang et al 2014 ; Kim et al 2018 ; Tong et al 2020 ). However, to the best of our knowledge, this is the first case to provide molecular evidence with a high match (99.6–100%) between SFTSV from a patient and questing ticks in the same living environment.…”
Section: Discussionmentioning
confidence: 99%
“…The presented results strongly support the link between SFTSV-infected ticks and the patient with SFTS with a history of tick bites. Some studies have identified SFTS pathogens in engorged ticks from patients with SFTS in the ROK and China (Wang et al 2014 ; Kim et al 2018 ; Tong et al 2020 ). However, to the best of our knowledge, this is the first case to provide molecular evidence with a high match (99.6–100%) between SFTSV from a patient and questing ticks in the same living environment.…”
Section: Discussionmentioning
confidence: 99%
“…SFTSV can evolve rapidly through genetic mutations and has already become a major threat to public health ( 3 ). There is no specific treatment for SFTSV, and the only method to prevent SFTSV infection and transmission is to avoid tick bites ( 10 ). Moreover, there is currently no vaccine for SFTSV.…”
Section: Introductionmentioning
confidence: 99%